Screening of Alzheimer’s disease with multiwavelength stokes polarimetry in a mouse model - Borovkova, Mariia; Sieryi, Oleksii; Lopushenko, Ivan; Kartashkina, Natalia; Pahnke, Jens; Bykov, Alexander V.; Meglinski, Igor V. (IEEE transactions on medical imaging)
The minimum histological criterion for the diagnostics of Alzheimer's disease (AD) in tissue is the presence of senile plaques and neurofibrillary tangles in specific brain locations. The routine procedure of morphological analysis implies time-consuming and laborious steps including sectioning and staining of formalin-fixed paraffin-embedded (FFPE) tissue. We developed a multi-spectral Stokes polarimetric imaging approach that allows characterization of FFPE brain tissue samples to discern the stages of AD progression without sectioning and staining the tissue. The Stokes polarimetry approach is highly sensitive to structural alterations of brain tissue, particularly to the changes in light scattering and birefringence. We present the results of the label-free non-destructive screening of FFPE mouse brain tissue and show several polarization metrics that demonstrate statistically significant differences for tissues at different stages of AD.